2022
DOI: 10.3390/ijms23147881
|View full text |Cite
|
Sign up to set email alerts
|

The Increase in the Drug Resistance of Acute Myeloid Leukemia THP-1 Cells in High-Density Cell Culture Is Associated with Inflammatory-like Activation and Anti-Apoptotic Bcl-2 Proteins

Abstract: It is known that cell culture density can modulate the drug resistance of acute myeloid leukemia (AML) cells. In this work, we studied the drug sensitivity of AML cells in high-density cell cultures (cell lines THP-1, HL-60, MV4-11, and U937). It was shown that the AML cells in high-density cell cultures in vitro were significantly more resistant to DNA-damaging drugs and recombinant ligand izTRAIL than those in low-density cell cultures. To elucidate the mechanism of the increased drug resistance of AML cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 80 publications
0
11
0
2
Order By: Relevance
“…It is well known that the main intracellular positive regulators of AML cell resistance to TRAIL-induced apoptosis are members of the BCL-2 and IAPs families, which block apoptosis at the mitochondrial and effector caspase levels [ 18 , 54 , 55 ]. PPI networks were built to determine the potential interaction of the identified hub genes with anti-apoptotic members of the IAPs and BCL-2 families.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the main intracellular positive regulators of AML cell resistance to TRAIL-induced apoptosis are members of the BCL-2 and IAPs families, which block apoptosis at the mitochondrial and effector caspase levels [ 18 , 54 , 55 ]. PPI networks were built to determine the potential interaction of the identified hub genes with anti-apoptotic members of the IAPs and BCL-2 families.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that in AML THP-1 cells under in vitro conditions, in a three-dimensional high-density culture simulating homotypic intercellular communication in the hyperplasia of leukemic blasts in the bone marrow, there was an increase in the production of proinflammatory cytokines, chemokines, and growth factors; activation of proinflammatory NF-kB-dependent signaling pathways; and a reversible increase in resistance to TRAIL-induced death and to the action of chemotherapeutic drugs [ 17 , 18 ]. In addition, we have shown that macrophagelike clones THP-1ad with constitutive resistance to TRAIL-induced death appear in a three-dimensional high-density culture of these cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, PL and paclitaxel have synergistic cytotoxic effects on human intestinal cancer cells [ 36 ], and PL can also synergistically enhance the anticancer effects of oxaliplatin on human colorectal cancer [ 37 ]. All of these chemical drugs, including ARA-C [ 38 40 ], cause oxidative stress. Critically, they also activate the NF-κB signalling pathway as a mechanism of chemoresistance [ 41 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Bcl-2 and nuclear factor kappa B (NF-KB) pathways are frequently dysregulated, which activates the defective apoptotic machinery. Bcl-2 is a thoroughly researched anti-apoptotic protein that is also a major contributor to drug resistance [156]. These factors together imply that Bcl-2 may be a good target for reversing medication resistance.…”
Section: Apoptosis Targetingmentioning
confidence: 99%